THE ROLE OF INSTRUCTORS IN IMPROVING PROFESSIONALISM OF POLRI INTERVIEWS THROUGH EDUCATION AND TRAINING - Dwi Suciati (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
Training is a short-term education process that uses systematic and organized procedures. Training will be carried out well and correctly and smoothly as planned if supported by adequate education standards. The role of the Instructor is very supportive in enhancing the professionalism of the POLRI Police Officer through the Education and Training Center at the Cisarua National Police, West Java Regional Police is the theme to be studied. The theoretical basis used in this study is the role, coordination and professionalism based on theories and concepts from: 1) Role Theory; 2) Coordination Theory; 3) Professionalism Theory. The research method used is descriptive qualitative, data collection through: observation, interviews, documentation, literature study and questionnaire. The results of the study were obtained: 1) Efforts carried out by carrying out gradual coordination, the appointment of educators: educators must have academic competence, educator competence, have educator certification, and be physically and mentally healthy; 2) Coordination between educators using training management through stages: Planning, pengoranisasian, implementation and control; and 3) The role of the instructor contributes positively to the ability of the trainees which will have an impact on improving the quality of the National Police Officer.